Diffusion coefficients of polar organic compounds in agarose hydrogel and water and their use for estimating uptake in passive samplers - Urík, Jakub; Paschke, Albrecht; Vrana, Branislav (Chemosphere, 2020)
Diffusion coefficient (D) is an important parameter for prediction of micropollutant uptake kinetics in passive samplers. Passive samplers are nowadays commonly used for monitoring trace organic pollutants in different environmental matrices. Samplers utilising a hydrogel layer to control compound diffusion are gaining popularity. In this work we investigated diffusion of several perfluoroalkyl substances, currently used pesticides, pharmaceuticals and personal care products in 1.5% agarose hydrogel by measuring diffusion coefficients using two methods: a diffusion cell and a sheet stacking technique. Further, diffusion coefficients in water were measured using Taylor dispersion method. The sheet stacking method was used to measure D at 5, 12, 24, and 33 °C in order to investigate temperature effect on diffusion. Median D values ranged from 2.0 to 8.6 × 10-6 cm2 s-1 and from 2.1 to 8.5 × 10-6 cm2 s-1 for the diffusion cell and sheet stack methods respectively. For most compounds, the variability between replicates was higher than the difference between values obtained by the two methods. Rising temperature from 10 to 20 °C increases the diffusion rate by the factor of 1.41 ± 0.10 in average. In water, average D values ranged from 3.03 to 10.0 × 10-6 cm2 s-1 and were comparable to values in hydrogel, but some compounds including perfluoroalkyl substances with a long aliphatic chain could not be evaluated properly due to sorptive interactions with capillary walls in the Taylor dispersion method. Sampling rates estimated using the measured D values were systematically higher than values estimated from laboratory sampler calibration in our previously published study, by the factor of 2.2 ± 1.0 in average.
Keywords: pesticidy; Temperature; hydrogely; Environmental Monitoring; sefarosa; teplota; Polar organic compounds; DGT; Diffusion coefficient; Pesticides; difuze; monitorování životního prostředí; Kinetics; biologický transport; Diffusion; voda; organické látky; Organic Chemicals; Cosmetics; Water Pollutants, Chemical; Hydrogels; kosmetické přípravky; Sepharose; Agarose hydrogel; Water; Passive sampling; Taylor dispersion; kinetika; Biological Transport; chemické látky znečišťující vodu